Relationship between creative thinking and anxiety among adolescent boys and girls in Tehran, Iran - Tabrizi, Elaheh Ahadnejad; Abu Talib, Mansor; Yaacob, Siti Nor (Center for Promoting Ideas, 2011)
Anxiety disorders are the most common mental, emotional and behavioral problems that occur during adolescence. This research determines the relationship between creative thinking and anxiety among Iranian adolescents in Tehran. The study used multi-staged cluster random sampling method in the 517 male and female adolescents aged 12 to 15 years. The Abedi Creativity Test Questionnaire (ATC) was used to assess the creativity thinking and the Revised Children’s Manifest Anxiety Scale (RCMAS) for the anxiety level of the respondents. The results of this study indicated no significant differences in anxiety between girl and boy adolescents also, also no significant correlation between age and birth order with anxiety. Furthermore, in this research high correlation was found between creative thinking and anxiety among adolescents. Since creative thinking may help a person reduce anxiety, the findings may help encourage scholars and practitioners especially in Iran to use creative learning methods to lessen anxiety.